Countering violent extremism in Kenya: community, state, and security perspectives - Githigaro, John Mwangi (Lexington Books, 2024)
"This book examines how various stakeholders, including organizations and security actors, perceive the threats of extremism and the associated effects of countermeasures adopted within Kenya. It addresses the evolution of counter-terrorism interventions as well as the perceptions of the efficacy and effectiveness of counter-terrorism measures"--